Inequalities in the practice of physical activity in the city of São Paulo between 2003 and 2015: Evidence from a population-based study among older adults - Bruno Holanda Ferreira; Camila Nascimento Monteiro; Tatiane Kosimenko Ferrari Figueiredo; Margareth Guimarães Lima; Chester Luiz Galvão Cesar; Moisés Goldbaum; Olinda do Carmo Luiz (Archives of Public Health)
Abstract Background Regular physical activity is essential for the health and quality of life of older adults, helping to prevent non-communicable diseases and maintain autonomy. However, sociodemographic factors influence physical activity levels, leading to disparities in access and adherence. This study aimed to analyze changes in the frequency of physical activity and sociodemographic inequalities among older adults living in Brazil, using data from two health surveys. Methods The information on older adults (60 years or older) was obtained from two Health Surveys (ISA-Capital) conducted in the city of São Paulo, Brazil, in 2003 and 2015. The variables analyzed included sociodemographic characteristics and physical activity levels, considering the combined domains of leisure-time and transportation. Prevalence and 95% Confidence Intervals (95% CI) were calculated, and comparisons were made via crude and adjusted Prevalence Ratios (PR) by Poisson regression. Results Between 2003 and 2015, the prevalence of sufficient physical activity increased from 20.5% to 30.1%, representing a percentage change of 46.8%. When stratified by sociodemographic characteristics, the 2015 survey showed a significant increase in older adults with a sufficient level of physical activity concentrated among individuals aged 60–69 years (PR = 1.43; 95%CI 1.10–1.86), male (PR = 1.45; 95%CI 1.10–1.91), with partner (PR = 1.42; 95%CI 1.08–1.88), with up to 3 years of education (PR = 1.53; 95%CI 1.11–2.09), and who self-identified as race/skin color black or brown (PR = 1.70; 95%CI 1.12–2.59), when compared to their respective counterparts in the 2003 survey. Conclusions Overall, over 12 years, the prevalence of older adults achieving sufficient physical activity levels increased, although unevenly, highlighting the need for policies and interventions to promote more significant equity in access to physical activity opportunities. Significance/Implications These findings highlight the persistent inequalities in physical activity, emphasizing the need for targeted policies and interventions to ensure equitable access to physical activity opportunities among older adults.